Cross-Disciplinary Synergy: The Collaborative Role of Lecturers in PKM for Optimizing the Tri Dharma - Agus Suryanto; Rettagung Diana; Ria Fajar NurHastuti; Ayu Fitriyah; Dyah Erlina Sulistyaningrum; Amrih Yuwono; Sunarso Sunarso; Dendy Eta Mirlana; Tri Rahayuningsih; Ayuba Olaniyi Jibril (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The community service program or PKM is a strategic initiative aimed at developing student potential while serving as a platform for implementing the Tri Dharma of Higher Education. This article examines the collaborative role of interdisciplinary lecturers in mentoring PKM and their contribution to optimizing education, research, and community service. Using a descriptive-qualitative approach, the discussion focuses on how synergy among lecturers from diverse academic backgrounds enhances the quality of proposals, strengthens applied research, and promotes innovative solutions for society. Such collaboration not only broadens students’ perspectives but also reinforces the role of lecturers as key agents in the advancement of impactful and relevant knowledge. The findings indicate that lecturer collaboration in PKM plays a crucial role in fostering a productive academic environment and in achieving sustainable outcomes in the Tri Dharma. Therefore, institutional support, incentive policies, and a structured collaborative ecosystem are essential for success.